MEMBANGUN BUDAYA SEKOLAH YANG PRODUKTIF DI MASA PANDEMI COVID 19 - Astuti, Astuti (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2022)
School culture is a description of the values applied in schools, norms that exist and are enforced in schools. Various dimensions and elements of school culture actually return to the role of organizational members to create and influence it. The culture of Athirah Bone Islamic Junior High School was built directed at achieving the predetermined vision and mission, determining and implementing school culture, carrying out monitoring and evaluation. The basic principles that are used as references in developing school culture are the working principles of worship, customer appreciation, the sooner the better, and being active together. The right school culture during the Covid-19 Pandemic is; A culture of sincerity at work, Fast culture at work, Work culture hard, honest culture, discipline culture, cooperation culture, respecting price culture, never giving up culture, open culture, reminding each other culture, religious culture, sincere culture. The challenges and solutions in building a productive school culture during the Covid 19 Pandemic at Athirah Bone Islamic Junior High School are time and place (learning and services are carried out online) and direct communication, so the solution is to maximize the use of technology by using various online learning and service applicatio